ARTISTIC DECORATIONS AND TYPES OF PAINTINGS OF THE SHAHI-ZINDA ENSEMBLE (Academicia Globe: Inderscience Research, 2022)
Today, the preservation and restoration of architectural monuments in our country is one of the most important issues. The subject of the article is the types of the buildings of the complex Shohi-Zinda, their specificity are described. The memorial decorations in the tombs of the dungeon reflect the evolution over several hundred years